1993
DOI: 10.1002/j.1460-2075.1993.tb06152.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the intronic IgH enhancer and its flanking sequences differentially affect accessibility of the JH locus.

Abstract: To investigate the role of intronic immunoglobulin heavy chain (IgH) enhancer (E mu) in generating accessibility of the JH locus for VDJ recombination, we generated ES cells in which E mu or its flanking sequences were mutated by replacement with or insertion of an expressed neor gene. Heterozygous mutant ES cells were used to generate chimeric mice from which pre‐B cell lines were derived by transformation of bone marrow cells with Abelson murine leukemia virus (A‐MuLV). Comparison of the rearrangement status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 45 publications
3
133
1
Order By: Relevance
“…Transcriptional activation may therefore target immunoglobulin genes for V(D)J recombination. In agreement with this hypoth esis, V(D)J recombination is impaired by germ-line dele tion of the intronic enhancers of the IgH locus (Chen et al 1993;Serwe and SabUtzky 1993) and IgU gene (Takeda et al 1993) or by the lack of the Ep enhancer on transgenic recombination substrates (Ferrier et al 1990). As both intronic enhancers do not contain any high-af finity binding sites for BSAP (Barberis et al 1990), it is unlikely that Pax5 mediates its effect on V(D)J recombi nation by direct interaction with these regulatory re gions.…”
Section: Paxs and The B-cell-specific Control Of V(d)j Recombinationmentioning
confidence: 70%
“…Transcriptional activation may therefore target immunoglobulin genes for V(D)J recombination. In agreement with this hypoth esis, V(D)J recombination is impaired by germ-line dele tion of the intronic enhancers of the IgH locus (Chen et al 1993;Serwe and SabUtzky 1993) and IgU gene (Takeda et al 1993) or by the lack of the Ep enhancer on transgenic recombination substrates (Ferrier et al 1990). As both intronic enhancers do not contain any high-af finity binding sites for BSAP (Barberis et al 1990), it is unlikely that Pax5 mediates its effect on V(D)J recombi nation by direct interaction with these regulatory re gions.…”
Section: Paxs and The B-cell-specific Control Of V(d)j Recombinationmentioning
confidence: 70%
“…Some substrates did have discordant effects on these properties; whereas some substrates were transcriptionally active but recombinationally silent (34,35), others were transcriptionally silent but recombinationally active (36). Additionally, a genetically modified heavy chain locus was developmentally demethylated but recombinationally silent (37). Therefore, transcription and demethylation per se are not simply permissive for rearrangement, but specific enhancer sequences and cognate binding factors must be critical.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our findings at the kappa locus. Moreover, recent studies using an episomal recombination substrate demonstrated that the repression of recombination by methylation could be overcome, at least in part, by changes in chromatin structure, suggesting a role for specific factors in remodeling chromatin for recombination (37).…”
Section: Discussionmentioning
confidence: 99%
“…1). The first of these, E , is found in an intron separating the V region and C region coding sequences and, although initially discovered because of its ability to enhance transcription from the promoter of an assembled IgH gene, it has since been shown to be essential for efficient V-D-J recombination (3)(4)(5)(6)(7)(8)(9). The other four enhancers lie at the far 3Ј end of the IgH locus and have been shown to contribute substantially to IgH gene transcription in Ig-secreting cells as well as play an important role in CSR (10,11).…”
Section: Transcription Of a Productively Rearranged Ig Vdjc␣ Does Notmentioning
confidence: 99%